Too far to go? Does distance determine study choices? - Stefan Denzler; Stefan C. Wolter (Institute for the Study of Labor (IZA), 2011)
A number of studies have long shown that the probability of studying at university is influenced by the distance to the next university. This study shows for the first time that distance to university also influences the choice of subject/faculty and institution. Moreover, these findings are important because the distance effect in terms of these decisions is associated with significantly less risk of endogeneity than the effect in the analysis of the willingness and ambition to attend university. The results also show that distance does not influence study choices among students from the highest socioeconomic group, a finding that further indicates that distance to university is an expression of differences in the cost of a university education.
urn:nbn:de:101:1-201105306388
Keywords: I21; I23; R10; 330; distance-to-university; subject choice; university choice; Switzerland